Knowledge and Attitude on Obstetric Effects of Female Genital Mutilation among Maasai Women in Maternity Ward at Loitokitok Sub-County Hospital, Kenya - Keddy Wanjiru Muchene; Irene Gacheri Mageto; Joyce Jebet Cheptum (Obstetrics and Gynecology International)
Background. Female genital mutilation (FGM) is one of the most harmful traditions still practiced in many parts of the developing world, including Kenya. The practice leads to permanent and irreversible health damages; however, knowledge and attitude of women towards its obstetric effects is scarce. Aim. The objective of this study was to determine knowledge and attitude of women towards obstetric effects of FGM among Maasai women. Methods. A hospital-based cross-sectional study was conducted at Loitokitok Sub-County Hospital among 64 Maasai women who had undergone FGM. Systematic sampling was employed to identify the respondents. Data were collected using a pretested semistructured questionnaire and analyzed through Statistical Package for the Social Sciences (SPSS) version 20.0 based on frequencies and percentages. Qualitative data were coded and categorized and thematic analysis was done. Results. Half of the women were knowledgeable on obstetric effects of FGM. Majority of them, 81% (n=52), sustained perineal tears during childbirth while 53% (n=34) had postpartum hemorrhage. Majority of the respondents, 81% (n=51), had negative attitude towards FGM and 87% (n=31) would not encourage their daughters to be circumcised. Most of them, 64% (n=23), disagreed that circumcision made one a respectable woman. Conclusion. Obstetric effects of FGM were fairly known and there was negative attitude towards FGM practice.